Comparison of BTX Profiles and Their Mutagenicity Assessment at Two Sites of Agra, India - Vyoma Singla; Tripti Pachauri; Aparna Satsangi; K. Maharaj Kumari; Anita Lakhani (The Scientific World Journal)
In the present study, the concentrations of three volatile organic compounds (VOCs), namely, acronym for benzene, toluene, and xylenes (BTX) were assessed because of their role in the tropospheric chemistry. Two representative sites, a roadside and a petrol pump, were chosen for sample collection. VOCs were collected using SKC-activated charcoal tubes and SKC personal sampler and characterized by gas chromatograph using flame ionization detector. Among BTX, benzene had the highest concentration. At the roadside, mean concentration of benzene, toluene, o-,m-xylene, and p-xylene were 14.7 ± 2.4 μgm−3, 8.1 ± 1.2 μgm−3, 2.1 ± 0.8 μgm−3, and 5.1 ± 1.2 μgm−3, respectively. At the petrol pump, the mean concentrations of benzene, toluene, o-,m-xylene and p-xylene were 19.5 ± 3.7 μgm−3, 12.9 ± 1.1 μgm−3, 3.6 ± 0.5 μgm−3 and 11.1 ± 1.5 μgm−3, respectively, and were numerically higher by a fraction of 2. Monthly variation of BTX showed maximum concentration in winter. Inter-species ratios and inter-species correlation indicated traffic as the major source of BTX. Extracts of samples were positive in both Salmonella typhimurium tester strains TA98 and TA100 without metabolic activation suggesting the presence of direct mutagens in ambient air that can cause both frame-shift and base-pair mutation. The mutagenic response was greater for TA100 than TA98 suggesting greater activity for base-pair mutagenicity than frame-shift mutagenicity and was found to be statistically significant.